Effects of Sacha Inchi Tempeh on Oxidative Stress in Rats with Metabolic Syndrome - Afifah, Diana Nur; Nafisah; Anjani, Gemala; Syauqy, Ahmad; Mahati, Endang; Astawan, Made; Rahmawati, Irma Sarita (Indonesian Journal of Human Nutrition, 2024)
Metabolic syndrome is a condition caused by metabolic disorders such as overweight, obesity, lack of physical activity, and genetic factors. Increased ROS production in metabolic syndrome causes oxidative stress characterized by decreased antioxidant capacity, increased MDA, and decreased SOD enzymes. Sacha inchi has a high ALA content that can increase omega-3 levels, tocopherols, and antioxidants that can help protect liver tissue from damage caused by oxidative stress in metabolic syndrome.The purpose of this study was to look at how sacha inchi tempeh affected the levels of malondialdehyde, superoxide dismutase enzyme, and overall antioxidant capacity in rats with metabolic syndrome brought on by a diet high in fat and fructose. The method used in the research is an experiment with a pre-and post-control group design on Wistar strain white rats with metabolic syndrome induced by HFFD, with the intervention of sacha inchi tempe (0.9 g; 1.8 g; 3.6 g) for 5 weeks (35 days). The results of the study with paired T-tests were that there was a significant difference in TAC levels before and after the intervention in the intervention group with a p-value of <0.05 compared to the healthy group. MDA and SOD enzyme levels in rat liver tissue also were significant improvement with a p-value of <0.05. When compared to simvastatin medication therapy, sacha inchi tempeh at a dose of 3.6 g had the best results. Therefore, it is established that sacha inchi tempeh is beneficial as a nutraceutical meal in reducing oxidative stress in individuals suffering from metabolic syndrome.